Self-concept integration and differentiation in subclinical individuals with dissociation proneness. Issue 6 (2nd November 2017) - Chiu, Chui-De; Chang, Jen-Ho; Hui, Chin Ming
Abstract: Dissociative pathology is characterized by an altered sense of self. Still, it remains unclear (a) whether the altered sense of self is also associated with non-pathological dissociation as well and (b) whether this potential association is an intrinsic connection or a consequence of other related constructs, including childhood trauma. This study addresses this question by examining how self-concept organization may differ among individuals with different levels of dissociation proneness. The structure of self-concept was operationalized by various indexes of self-concept integration and differentiation. Results showed that individuals high in dissociation proneness have lower self-concept clarity and compartmentalize self-aspects with more polarized evaluations. Notably, the association between dissociation proneness and evaluative self-compartmentalization held after controlling for childhood trauma, anxiety, and depression. This characteristic self-concept organization can be an attribute of non-pathological dissociation.